Regulatory response? Tracking the influence of technological developments on privacy regulation in Denmark from 2000 to 2011. Issue 3 (21st October 2013) - Helles, Rasmus; Lomborg, Stine
<x xml:space="preserve">Abstract</x> This article presents an empirical study of the developments in the regulation of privacy in Denmark over the past decade, from 2000 to 2011. During this period, technologies for harvesting, storing, and analyzing logs of personal data, often compiled by digital systems in so‐called big data archives, have gradually become central resources in contemporary business intelligence. Through a historical analysis of cases decided upon by the Danish Data Protection Agency, we develop an empirical baseline for assessing changes to the regulatory practice concerning privacy. We use Bordewijk and Kaam's (1986) classification scheme of information flows as a conceptual model to examine which kinds of information flows give rise to regulatory consolidation and change, and identify practices of personal data processing that seem to escape regulatory action.